Analisis Pemanfaatan Teknologi Informasi dan Komunikasi (TIK) Digital untuk Pemasaran Ikan Skala Mikro : Systematic Literature Review - Leonardi, Aska; Sjafri, Aida Vitayala; Saleh, Amiruddin; Fatchiya, Anna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Fish is a perishable commodity, so it takes fast time to reach consumers. However, many obstacles are experienced in marketing fish, such as market access, natural barriers, including distance and travel time, institutional barriers including legal restrictions on entry, tariffs, and quotas. This study was conducted to describe the current state of research on the use of ICT in fish marketing to recommend research on fish marketing communications in the future. This study uses a literature review method, by analyzing 22 journal articles based on relevant keyword searches. All samples were then described qualitatively. The results show that the adoption of mobile phones, especially from an economic perspective, can have an impact on increasing market efficiency. The main focus that becomes an opportunity to contribute to a fish marketing communication strategy is research on the competence of fish marketers in using ICT.